Pore–scale analysis of supercritical CO2–brine immiscible displacement under fractional–wettability conditions. (April 2019) - Bakhshian, Sahar; Hosseini, Seyyed Abolfazl
Highlights: A pore-scale simulation of scCO2 –brine drainage and imbibition was studied in a realistic rock model. The effect of wettability heterogeneity on scCO2 immiscible displacement dynamics, as well as its capillary trapping mechanism, was investigated. Heterogeneous distribution of CO2 –wet regions in the rock leads to more dispersed fluid distribution and, hence, higher interfacial area between fluid phases and rock surface at any given scCO2 saturation. Spatial distribution of wettability controls scCO2 entrapment patterns and spatial distribution of residual scCO2 clusters during brine flooding. Abstract: The objective of this study was to investigate the effect of wettability heterogeneity on pore–scale characteristics of Supercritical (sc) CO2 displacement dynamics and its capillary trapping mechanism during a scCO2 –brine drainage and imbibition cycle. A multiphase lattice Boltzmann (LB) model was employed to simulate scCO2 –brine flow in rock samples of Tuscaloosa sandstone taken from the Cranfield CO2 injection site. Using a spectral method, we adopted various wettability fields to generate rock samples containing distributed CO2 –wet regions. To gain a better insight into the effect of fractional wettability on scCO2 displacement patterns during drainage, we quantified the evolution of scCO2 interface with brine and rock surface for samples with various wettability heterogeneities. In addition, the effect of heterogeneous wettability on the drainage relative permeability and capillary pressure curves has been investigated in this study. According to our results, heterogeneous distribution of CO2 –wet regions in the rock leads to more dispersed fluid distribution and, hence, more tortuous flow paths, resulting in higher interfacial area between fluid phases and rock surface at any given scCO2 saturation. Furthermore, the spatial distribution of wettability controls the scCO2 entrapment pattern and spatial distribution of residual scCO2 clusters during brine flooding. In fractional–wet samples, residence of scCO2 phase in CO2 –wet regions creates more trapped scCO2 clusters, suppressing the connectivity of the CO2 phase, thus enhancing more residual trapping. Our results imply that the total number of scCO2 clusters and, as a result, their residual trapping, increases as the fraction of CO2 –wet regions becomes larger, leading to a larger surface area of scCO2 with brine and rock surface, potentially, facilitating the likelihood of long-term dissolution and mineral trapping.